2017
DOI: 10.1016/j.jascer.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Unique crystallization behavior of sodium manganese pyrophosphate Na2MnP2O7 glass and its electrochemical properties

Abstract: Crystallization behavior of Na 2 MnP 2 O 7 precursor glass was examined. Layered type Na 2 MnP 2 O 7 was formed at 461 • C for 3 h in N 2 filled electric furnace. Irreversible phase change was confirmed from layered Na 2 MnP 2 O 7 to ␤-Na 2 MnP 2 O 7 over 600 • C. At 650 • C crystallized phase was completely changed to ␤phase. By means of charge and discharge testing it is found that layered Na 2 MnP 2 O 7 is also active as cathode in sodium ion batteries. We found glass-ceramics technology is one of the suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Our research group has previously reported the synthesis of different active materials for LIBs [19][20][21][22][23][24][25][26] and SIBs [27][28][29][30][31][32][33] via the crystallisation of phosphate glass using a melting method. In general, the crystallisation of glass proceeds via a continuous process of crystal nucleation and growth from a homogeneous inorganic matrix 34,35 .…”
mentioning
confidence: 99%
“…Our research group has previously reported the synthesis of different active materials for LIBs [19][20][21][22][23][24][25][26] and SIBs [27][28][29][30][31][32][33] via the crystallisation of phosphate glass using a melting method. In general, the crystallisation of glass proceeds via a continuous process of crystal nucleation and growth from a homogeneous inorganic matrix 34,35 .…”
mentioning
confidence: 99%
“…The substitution of Fe 2+ ions in the Na 2 FeP 2 O 7 crystal by Mn 2+ ions is effective for increasing the discharge voltage of the battery. In our previous study, the crystallization of Na 2 MnP 2 O 7 exhibits two different structural polymorphs so‐called metastable layered‐ (designated here as L‐) Na 2 MnP 2 O 7 and β‐Na 2 MnP 2 O 7 depend on the heat‐treatment temperature of the base glass . On the other hand, the crystallization of Na 2 FeP 2 O 7 only shows the formation of β‐phase.…”
Section: Introductionmentioning
confidence: 97%
“…In our previous study, the crystallization of Na 2 MnP 2 O 7 exhibits two different structural polymorphs so-called metastable layered-(designated here as L-) Na 2 MnP 2 O 7 and β-Na 2 MnP 2 O 7 depend on the heat-treatment temperature of the base glass. [21][22][23] On the other hand, the crystallization of Na 2 FeP 2 O 7 only shows the formation of β-phase. Tanabe clarified that the compositional limit of the formation of L-polymorph in the pseudo-binary system of xNa 2 MnP 2 O 7 -(1−x)Na 2 FeP 2 O 7 exists at x = 0.75.…”
Section: Introductionmentioning
confidence: 99%
“…Yamauchi et al [8,9] proposed a new prototype Na-ASSBs, in which Na 2 FeP 2 O 7 glass-ceramics and β-alumina solid solutions are used as cathode active materials and solid electrolytes, respectively. Na 2 FeP 2 O 7 glass and its derivative glassceramics exhibit viscous flows during the crystallization process and can be adhered to solid electrolytes at a low temperature of 500 • C without any external pressurization [10][11][12][13][14][15]. The battery's internal resistance was successfully reduced by optimizing the crystallization process of Na 2 FeP 2 O 7 glass, and the battery operation at −20 • C was demonstrated [9].…”
Section: Introductionmentioning
confidence: 99%